WAYS TO IMPROVE CONTROL OVER THE EXPENDITURE OF BUDGET FUNDS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the theoretical and practical aspects of improving financial control over the expenditure of budget funds in Uzbekistan. It highlights the importance of financial control in ensuring economic stability, efficient public finance management, and increasing public trust in the state. The study analyzes existing shortcomings in the national system, such as insufficient development of internal audit, duplication in the activities of control bodies, and limited transparency. International practices, including digital audit, risk-based control, and civil society participation, are reviewed with a focus on their applicability to Uzbekistan’s context. The article proposes key measures such as adopting a unified law on state financial control, strengthening internal audit systems, introducing digital technologies (including blockchain), and enhancing public oversight through platforms like the “Open Budget” portal.